Timespace for Emotions: Anachronism in Flaubert, Bal/Williams Gamaker, Munch and Knausgård - Hernández Navarro, Miguel Ángel (Text Matters: A Journal of Literature, Theory and Culture, 2017)
Quoting Flaubert through time, Mieke Bal and Michelle Williams Gamaker’s Madame B brings Madame Bovary’s reflections on love and emotions to the present day, in a productive anachronism. Their work produces an intertemporal space where the past is relevant for the present, and the present enables us to understand the past. Intimacy and routine are central in their exploration of Flaubert’s contemporaneity. Those issues are precisely one of the keys in Karl Ove Knausgård’s project of literary autobiography, where he expands narration foreclosing the ellipsis and giving visibility to small things and emotions; a project with some resonances with Munch’s crude-obscene uses of intimacy. This essay explores how both proposals, Bal and Williams Gamaker in film, and Knausgård in literature, can serve us to connect present and past sensibilities and, more than that, demonstrate resistances to the hegemonic discourses of temporality.